Trade finance in Qatar: blockchain and economic diversification - Andrew Dahdal (17128879) (2020)
Trade finance helps businesses deal with abnormal cash flows whilst managing counterparty risk and enhancing confidence in commercial transactions. It also allows parties to overcome trust barriers that may inhibit commercial activity in both a domestic and international commercial context. Globally, particularly among micro, small and medium enterprises (MSMEs), there exists a significant and widening unmet demand for documentary finance. Securing trade finance is laborious and time-consuming. For MSMEs, the trade finance application process alone, can be an insurmountable barrier that usually ends in rejection. By its nature, trade finance arrangements engage with decentralized stakeholders and diffused information sources across supply chains. Issuers and underwriters of trade finance instruments are required to draw on disparate elements of information, not merely during the application phase, but indeed throughout the life of a transaction. Blockchain technology is similarly decentralized and can capture information in a secure, transparent and immutable manner potentially improving and reinvigorating the trade finance space. As Qatar embarks on a strategy of widening its economic base away from a singular reliance on the hydrocarbon fuel sector, the introduction of blockchain technology holds the potential to overcome the transactional friction associated with trade finance. A more efficient and accessible trade finance sector will ultimately enhance the competitiveness of MSMEs whilst simultaneously fostering the growing FinTech sector in Qatar. Other Information Published in: Law and Financial Markets Review License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/17521440.2020.1833431